Analysis Of Qris Potential in Mobile Banking to Support Financial Inclusion in The Face of The Post-Pandemic Covid-19 Crisis: A UTAUT2 Model Approach - Musyaropah, Musyaropah; Sugianto, Sugianto; Shoolihah, Muhayyijah Fil Qurbah (Abdurrauf Social Science, 2025)
This study investigates the factors that influence the implementation of QRIS in Islamic bank mobile banking services in the post-COVID-19 context. Guided by the Extended Unified Theory of Acceptance and Use of Technology (UTAUT2), the research emphasizes the dynamics of Islamic finance and aims to identify aspects requiring further development in QRIS M-Banking. A total of 500 individual customers of Islamic banks who actively use mobile banking services across Indonesia participated in the study. The research employed a quantitative method with purposive sampling. Data were collected through a combination of open- and close-ended questionnaires and analyzed using SPSS 26. The results reveal that Social Influence, Facilitating Conditions, Hedonic Motivation, and Habit significantly affect Behavioral Intention to use QRIS M-Banking, while Performance Expectancy, Effort Expectancy, and Trust show no significant influence. These findings underline the importance of strengthening social and environmental support, improving system infrastructure, and enhancing features that encourage positive user habits and enjoyment in financial transactions. This study contributes theoretically by extending the application of UTAUT2 within the context of Islamic banking and post-pandemic financial behavior. Practically, it provides insights for Islamic banks to design strategies that foster higher QRIS adoption rates, while also offering recommendations for policymakers to strengthen digital financial inclusion and promote sharia-compliant payment systems. Abstrak: Penelitian ini bertujuan untuk mengkaji faktor-faktor yang memperkuat implementasi QRIS pada layanan M-Banking bank syariah pasca pandemi COVID-19. Penelitian ini menggunakan Extended Unified Theory of Acceptance and Use of Technology (UTAUT2) dengan fokus pada keuangan syariah, dan bertujuan untuk mengidentifikasi elemen-elemen yang memerlukan perbaikan pada QRIS M-Banking. Penelitian ini terdiri dari dua tahap. Tahap pertama bertujuan untuk memasukkan faktor-faktor yang mempengaruhi keinginan penggunaan QRIS M-Banking pasca pandemi COVID-19. Penelitian tahap kedua ini bertujuan untuk menyoroti faktor-faktor yang memerlukan pengembangan QRIS M-Banking untuk mempercepat dan meningkatkan keuangan syariah pasca pandemi COVID-19. Partisipan penelitian terdiri dari 500 nasabah individu bank syariah yang aktif menggunakan layanan M-Banking yang tersebar di berbagai wilayah di Indonesia. Metode penelitian yang dipilih adalah kuantitatif, dengan pendekatan pengambilan sampel menggunakan metode purposive sampling. Data dikumpulkan melalui kombinasi pertanyaan terbuka dan tertutup, kemudian dianalisis menggunakan software SPSS 26. Hasil analisis menunjukkan bahwa Social Influence, Facilitating Conditions, Hedonic Motivation, dan Habit mempunyai pengaruh yang signifikan terhadap variabel Behavioral Intention, sedangkan Performance Expectancy, Effort Expectancy, dan Trust tidak mempunyai pengaruh yang signifikan terhadap variabel Behavioral Intention. Kontribusi penelitian ini secara teoretis memperluas penerapan model UTAUT2 dalam konteks perbankan syariah dan perilaku keuangan pasca pandemi. Secara praktis, penelitian ini memberikan wawasan bagi bank syariah untuk merancang strategi yang mendorong adopsi QRIS lebih tinggi, serta menawarkan rekomendasi bagi pembuat kebijakan dalam memperkuat inklusi keuangan digital dan pengembangan sistem pembayaran syariah di Indonesia.